Explaining Gender Differences in Migrant Sorting: Evidence from Canada-US Migration - David Escamilla-Guerrero; Miko Lepistö; Chris Minns (Institute of Labor Economics (IZA), 2023)
Using newly digitized Canada-Vermont border crossing records from the early twentieth century, this paper identifies key factors that may explain differences in how female and male migrants sort by human capital across destinations. Earnings maximization largely explains sorting patterns among males, while gender discrimination has a large effect on the sorting of female migrants. Everything else equal, destinations with institutional and social environments that limited the participation of women in the labor market attracted a lower-skilled mix of both single females and couples. Although married women were typically tied to a spouse whose labor market opportunities determined the joint destination, we find evidence suggesting that their degree of agency in the destination choice increased with human capital.
Keywords: J61; N31; N32; 330; migration; sorting; gender; Canada; United States